Undergraduate learning in the field: Designing experiences, assessing outcomes, and exploring future opportunities. Issue 4 (2nd October 2021) - O'Connell, Kari; Hoke, Kelly; Berkowitz, Alan; Branchaw, Janet; Storksdieck, Martin
Abstract: Field learning experiences reach tens of thousands of undergraduate students annually, constituting their importance as components of undergraduate education and potential pathways for STEM education. Reports and planning efforts by national entities have highlighted the need to ground undergraduate field learning experiences in evidence-based practices, and to better understand the impacts of these experiences on students. In this study we describe the results of a national survey aimed at better understanding how instructors and directors at biological field stations, marine laboratories, and geoscience field camps are thinking about and designing programs, including learning strategies, student support, desired student outcomes, student assessment and program evaluation. This study is based on an online survey distributed in 2018 to a sample of directors and educators representing 163 undergraduate field learning experiences. The study achieved a satisfactory response rate of 31% ( n  = 563). The results of the study provide guidance on where support for improvement and research efforts should focus, including more intentional program design that considers student-centered and inclusive approaches and basic research on the impact of undergraduate field learning experiences on student learning more broadly (not just investigated in one program or course), both in terms of what the students learn (broadly defined) as well as how they learn, taking into account affective and cognitive gains. Such research can make productive use of the diversity of program types to investigate the link between student outcomes and student experiences.